Interaksi Faktor Lingkungan dan Sistem Budidaya terhadap Serangan Penyakit Karat Daun pada Tanaman Jagung - Putri, Diana (Jurnal Kridatama Sains dan Teknologi, 2025)
Corn is an important food crop in the world besides rice and wheat. In Indonesia, corn is not only used as food but also as animal feed and industrial materials, so the need for corn will continue to increase. Many obstacles are limiting factors in meeting the needs and productivity of corn, one of which is the attack of diseases such as corn leaf rust disease by Puccinia sp. This study aims to determine the incidence and severity of leaf rust disease attacks on monoculture and polyculture lands and to determine the importance of environmental factors on the development of the disease. The study was conducted in the experimental field and Phytopathology Laboratory of the Agroecotechnology Study Program, Campus III, Andalas University, Dharmasraya. The study was descriptive in nature using a survey method. Observation parameters included land conditions, symptoms of corn leaf rust, microscopic identification of pathogens, and the incidence and severity of the disease. The results showed that the pathogen causing leaf rust was identified as Puccinia polysora with symptoms of attack in the form of brownish yellow spots (pustules). The high incidence of the disease reached 100% while the severity reached 11.42% in polyculture lands and 15.00% in monoculture lands. This shows that the severity of corn leaf rust disease in the experimental land of the Agroecotechnology Study Program is included in the mild category